Vivências do enfermeiro no serviço de atendimento móvel de urgência: detalhes de um grande desafio - Thays Batista da Rocha (2013)
Front of change in the profile of the morbidity and mortality of the population and the advancement of mortality from external causes, such as violence and traffic accidents, the state was felt the need to structure health services with a focus on urgent and emergency care. So, has given the structuring of Network Urgencies Care in the Country, with the creation of the Mobile Emergency Service (SAMU), with works 24 hours, is an important link in constant movement between health services. In this context, showed the increase for labor camp for nurse, professional, already inserted in pre-hospital care (APH) since from its beginnings. This study aimed to analyze the particular situations that involve the everyday work life of nurses in different scenarios of Service Mobile Emergency from their life experiences. This is a descriptive and qualitative case study, in which 12 nurses from SAMU in Belo Horizonte, were interviewed by a semi-structured interview script and submitted to content analysis. Starting from the analysis, were constituted the categories: everyday work life of nurses of SAMU such scenario of relationships, which was subdivided in subcategories the teamwork as the basis of pre-hospital care, relation of the nurse of SAMU with the patients and families and relation of the nurse with the professionals of Network Health Care; and the categories peculiarities of the exercise of nurses in the SAMU, which was subdivided in subcategories details of the performance of the nurse of SAMU and challenges of everyday work life. The results showed that nurses maintain relationship with the doctor, nursing technicians and driver aider based on trust, on job security and on teamwork, aiming to meet the victim to quickly and resolute. In relationship with patients and families, the reports showed that despite the suffering and losses existing, the users express gratitude and respect. But, this could range as the time of the incident, may be expression of user dissatisfaction. In the contacts with other professionals in network, in most cases, there are conflicts principally due to the definition of the attributions of the different services. The nurse performs administrative and assistance activities. The peculiarities of APH and challenges reflected a stressful job and, at the same time, pleasurable by the recognition by the nature of work in urgencies that is done under pressure, climate variability and physical risks, chemical, biological and psychosocial factors such as violence in risky areas in addition, to being subject to pedestrians and traffic accidents. Among the challenges was found the necessity of know how to deal with the pain, the suffering and the death with readiness, quick thinking and assertive decision making, especially in the face of unpleasant images in scenes of care, and also find strategies to work in scenarios of urban violence in which are at risk their lives